Early-Term Outcomes of Off-Pump versus On-Pump Beating-Heart Coronary Artery Bypass Surgery - Velioglu, Yusuf; Isik, Mehmet (The Thoracic and Cardiovascular Surgeon, 2019)
Background The current study analyzed and compared early-term outcomes of off-pump versus on-pump beating heart coronary artery bypass surgery.Methods From January 2011 to January 2018, a total of 736 patients underwent isolated first-time elective beating-heart coronary artery bypass surgery without the use of aortic cross-clamping and cardioplegic arrest at our institution, and they were included in this study. Data of patients were collected and retrospectively analyzed. Patients were divided into two groups according to the use of cardiopulmonary bypass during the operation, as off-pump group (n = 399) and on-pump beating-heart group (n = 337). Both groups were compared with each other in terms of preoperative, intraoperative, and postoperative data.Results Groups were statistically similar with regard to baseline clinical characteristics and demographics. When compared with off-pump group, on-pump beating-heart group had a greater number of distal bypass, longer length of hospital stay, and lower postoperative hematocrit level, and received more blood product transfusion. No statistically significant differences were detected between the groups with respect to mortality and postoperative complications except for atrial fibrillation. Atrial fibrillation was significantly frequent in on-pump beating-heart group.Conclusion Our study suggested that off-pump and on-pump beating-heart coronary artery bypass procedures had similar early mortality and major complication rates except for atrial fibrillation. However, it seemed that off-pump procedure was superior to on-pump beating-heart procedure with regard to length of hospital stay, blood product transfusion, and atrial fibrillation development. Further prospective randomized studies with larger patient series are needed to support our research and attain more accurate data.
Keywords: coronary artery bypass grafting; cardiopulmonary bypass; off-pump surgery; outcomes